Impact of tumor diameter on post-radiofrequency ablation survival and local progression risk in patients with colorectal cancer lung metastasis - YING Leilei, LI Kening, CHEN Chao, WANG Ying, HUANG Haozhe, WANG Biao, LI Wentao, HE Xinhong (Zhongguo aizheng zazhi, 2025)
Background and purpose: Approximately 30% of patients with metastatic colorectal cancer (CRC) develops pulmonary metastasis, yet less than 10% are eligible for surgical resection. Radiofrequency ablation (RFA) serves as an alternative therapy for non-surgical candidates, but the relationship between its efficacy and tumor diameter remains controversial. This study aimed to investigate the impact of tumor size on survival outcomes and local progression risk in CRC patients with pulmonary metastasis after RFA, and to validate the clinical utility of a 3 cm threshold for prognosis. Methods: This retrospective study included CRC patients with pulmonary metastasis who underwent RFA at Fudan University Shanghai Cancer Center between January 2016 and December 2024. Patients were stratified into two groups based on maximum lesion diameter: ≤3 cm (Small group) and 3-5 cm (Large group). Patient inclusion criteria: ⑴ pathologically confirmed lung metastases originating from CRC, with metastases limited to the lungs or extra-pulmonary metastatic lesions having been radically treated; ⑵ maximum lesion diameter <5 cm; ⑶ complete clinical data available; ⑷ complete imaging data available, including computed tomography (CT) images during ablation and contrast-enhanced CT images during postoperative follow-up; ⑸ follow-up time of at least >6 months after RFA; ⑹ technical complete ablation; ⑺ fewer than 3 pulmonary metastatic lesions. Exclusion criteria: ⑴ target lesions previously treated with local therapies such as RFA or radiotherapy; ⑵ patients unable to tolerate RFA; ⑶ patients with follow-up time <6 months after RFA. Three senior interventional physicians performed percutaneous RFA under guidance of a 64-slice spiral CT scanner. Chest contrast-enhanced CT scans obtained 1 month after RFA were used as the baseline, followed by contrast-enhanced CT scans every 3 months for 1 year, then every 6 months for subsequent follow-up. This study was approved by the medical ethics committee of Fudan University Shanghai Cancer Center (ethical approval number: 2108241-11). Primary endpoints included overall survival (OS), progression-free survival (PFS), and local tumor progression (LTP). Kaplan-Meier analysis and multivariate COX regression were employed to evaluate the independent prognostic value of tumor size. Results: A total of 134 patients who met the inclusion criteria were ultimately enrolled, including 77 in the Small group and 57 in the Large group. With a median follow-up of 35 months, the ≤3 cm group demonstrated superior 1-, 3-, and 5-year OS rates (100.0%, 95.1%, 74.2%) compared to the 3-5 cm group (94.7%, 36.8%, 27.0%, P<0.0001), and the ≤3 cm group demonstrated superior 1-, 3-, and 5-year PFS rates (90.9%, 34.4%, 23.3%) compared to the 3-5 cm group (13.8%, 0.0%, 0.0%, P<0.000 1). The ≤3 cm group also exhibited significantly lower 1-, 3-, and 5-year LTP rates (0.0%, 19.7%, 33.6%) compared to the 3-5 cm group (46.0%, 75.5%, 75.5%, P<0.000 1). Multivariable analysis identified tumor diameter >3 cm as an independent predictor of worse OS [hazard ratio (HR)=6.49, 95% CI: 3.18-13.24, P<0.001], while elevated preoperative carcinoembryonic antigen (CEA) (≥5 ng/mL) correlated with shorter OS (HR=1.82, P=0.033). Conclusion: CRC patients with pulmonary metastasis and tumor diameters of 3-5 cm exhibited significantly inferior survival outcomes after RFA compared to the ≤3 cm group. A tumor diameter of 3 cm can serve as a critical threshold for selecting RFA indications, and combining preoperative CEA levels can optimize patient stratification.